A universal delta model - Barabucci, Gioele <1982> (Alma Mater Studiorum - Università di Bologna, 2013)
This thesis presents a universal model of documents and deltas. This model formalize what it means to find differences between documents and to shows a single shared formalization that can be used by any algorithm to describe the differences found between any kind of comparable documents.